The impact of the whole school evaluation on school management plan towards physical science learner performance at Sekhukhune, Limpopo, South Africa :The case of Malegale Circuit of Education - Mphahlele, Thokgela Millington (My University, 2018)
School Improvement Plan is introduced to improve learner performance in South Africa. This plan is integrated within the whole School Evaluation so as to enhance the quality of education in the country. Malegale Circuit of Education in Limpopo Province is central to the investigation. In terms of the Whole School Evaluation (WSE) schools are required to annually develop and implement a School Improvement Plan (SIP). As part of a SIP, a school should plan to monitor and examines at regular intervals, whether its practices and learner achievement are undergoing changes.SIP maps out the actions needed to bring about improvement. It is compiled annually after School Self-Evaluation (SSE). The focus areas used by school management teams to draw their School Improvement Plan (SIP) are: basic functionality of the school; leadership, management and communication; governance and relationships; quality of teaching and educators development; curriculum provision and resources; learner achievement; school safety, security and discipline; school infrastructure; and parents and community. It outlines the school’s strategies for improvement and sets clear targets of action. All the schools are obliged to draw their School Improvement Plan (SIP) in the curriculum of every subject. The programme helps in assisting towards improving performance in terms of quality of teaching and learning, educator development, curriculum provision and resources, learner achievement and school infrastructure. The study provides insight into the research design, qualitative case study which includes Semi-structured interviews, Document review, Field notes and Observation and quantitative in the form of questionnaires research paradigms, purposeful sampling, site selection, the participants, and data analysis. The members of the school management teams should be encouraged to implement School Improvement Plan in an effective and professional manner. The members of the school management team should be encouraged to appoint qualified physical science teachers to enhance the impact of whole school evaluation on school improvement plan. Government officials should be encouraged to monitor and evaluate the implementation of the whole school evaluation and school improvement plan, so as to enhance the teaching of Physical Science.
Thesis (M. Dev.) -- University of Limpopo, 2018.
Keywords: School evaluation; School management plan; Physical science; School districts -- South Africa -- Evaluation